Aggregation and stability of iron oxide and alumina nanoparticles: influences of pH and humic acid concentration - Nur Suraya Ahmad,; Shahidan Radiman,; Wan Zuhairi Wan Yaacob, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The scenario of released nanoparticles from consumer products into the environment especially natural waters has become a great concern nowadays. Assessing their aggregation and stability under environmental conditions is important in determining their fate and behavior in natural waters. The aggregation behavior of selected nanoparticles (iron oxide and alumina) was investigated at variable concentrations of humic acid (5, 10, 50 mg/L), and pH variation in solution. Dynamic light scattering was used to measure their z-average hydrodynamic diameter and zeta potential. Derjaguin-Landau-Verwey-Overbeak (DLVO) theory was used to explain the thermodynamic interactions between two particles. Then, the stability was evaluated by assessing their aggregation. The increasing of humic acid concentrations enhanced aggregation of iron oxide and alumina nanoparticles, particularly at low pH levels. The maximum aggregation was found in pH below the point of zero charge (PZC) due to electrostatic destabilization and electrostatic stabilization that took place at pH above the point of zero charge. Meanwhile, at pH point of zero charge, nanoparticles were coated with negative humic acid charged. From this study, properties of nanoparticles (size, surface charge, Hamaker constant) and environmental condition (humic acid concentration, pH) have their specific roles to control the fate and behavior of nanoparticles in environmental media.